MODERN METHODS OF MANAGING HOTEL SERVICE QUALITY AND IMPROVING EFFICIENCY - Sayfudinov Shuhratjon; Murodov Jahongir (Journal of Economics and Tourism Research, 2026)
Hotel service quality management is one of the key factors in the modern tourism industry. This article comprehensively analyzes innovative approaches to ensuring and improving the quality and efficiency of hotel services, the integration of digital technologies, advanced methods of customer experience management, and systems developed on the basis of international standards. The application of modern tools such as TQM (Total Quality Management), Six Sigma, Lean methodologies, artificial intelligence-based monitoring systems, Big Data analytics, and real-time customer feedback processing mechanisms in the hotel business, as well as their impact on economic efficiency and competitiveness, are examined. The research findings indicate that an integrated approach to quality management can increase service speed by 25–40%, significantly improve customer satisfaction, and optimize operational costs. The proposed models and recommendations have practical significance for the hotel industry in developing countries and contribute to sustainable development and the formation of a high-quality service culture.